Japanese experience of economic reforms / edited by Juru Teranishi and - "Teranishi, Juru (ed.)" and Kosai, Yutaka (ed.) (New York, 1993)
The Japanese Experience of Economic Reforms offers a renewed investigation into the process of economic reforms and stabilization in Japan after the Second World War. Each chapter reviews policy measures undertaken during this process, discusses their economic rationale, and evaluates their effectiveness. The authors point out a gradual, step-wise process and the government's emphasis on micro and supply-side issues as main characteristics of the Japanese experience. Relevance of the Japanese experience to the developing and post-socialist countries is also discussed.
Keywords: India economic policy 1945-1989